A balancing act times two: sensing and regulating cell envelope homeostasis in Bacillus subtilis. Issue 6 (20th November 2014) - Fritz, Georg; Mascher, Thorsten
Summary Bacterial cell wall homeostasis is an intricately coordinated process that ensures that envelope integrity is maintained during cell growth and division, but can also adequately respond to growth‐limiting conditions such as phosphate starvation. In Bacillus subtilis, biosynthesis of the two major cell wall components, peptidoglycan and anionic polymers, is controlled by a pair of paralogous two‐component systems, WalRK and PhoPR respectively. Favorable growth conditions allow for a fast rate of cell wall biosynthesis (WalRK‐ON) and the incorporation of the phosphate‐containing anionic polymer teichoic acids (PhoPR‐OFF). In contrast, growth‐restricted cells under phosphate‐limiting conditions reduce the incorporation of peptidoglycan building blocks (WalRK‐OFF) and switch from the phosphate‐containing teichoic acids to the phosphate‐free anionic polymer teichuronic acid (PhoPR‐ON). Botella et al. (2014) deepen our knowledge on the PhoPR system by identifying one signal that is perceived by its histidine kinase PhoR. In fast‐growing cells, intracellular intermediates of teichoic acid biosynthesis are sensed by the cytoplasmic Per‐Arnt‐Sim domain as an indicator of favorable conditions, thereby inhibiting the autokinase activity of PhoR and keeping the system inactive. Depletion of teichoic acid building blocks under phosphate‐limiting conditions relieves this inhibition, activates PhoPR‐dependent signal transduction and hence the switch to teichuronic acid biosynthesis.